Second shot - Dees, Cindy (Helen Warwick thriller, 2023)
"Retirement isn't easy for a former CIA assassin. For fifty-five-year-old Helen Warwick, it may be impossible. Even Helen's family doesn't know the true nature of the work she's done for decades--the secret black ops, the sanctioned executions. But her plan to spend time reconnecting with her grown children has just been blown up--along with her son's house--by hired killers. Why is she being targeted now--and by whom? Years of eliminating the nation's enemies one sniper bullet at a time have earned Helen powerful adversaries. Then there are mysterious new foes, including a psychopath dubbed The DaVinci Killer, who wages a twisted war with a rival serial killer to turn murder into art. And when he sets his sights on Helen, she may very well become his next exhibit. From homegrown spies to Russian mafia hitmen, Helen's ghosts don't just haunt--they kill. And staying alive long enough to make up for the past, and protect those closest to her, will take every ounce of skill she possesses ..."--